Hortas escolares urbanas: da produção de alimentos ao ensino da sustentabilidade ambiental - Melo, Tálita Nogueira Gonzaga (2022)
The urban and peri-urban practice has been strengthened in multiples spaces of the cities, through multiple entry points, which range from self-consumption and food supplementation, alternative employment and income for vulnerable groups, solutions for environmentally resilient cities, to an opportunity to practice social and environmental education activities. Considering this last aspect, the theme of this research is the study of the use of urban school gardens as a pedagogical tool for environmental sustainability, integrated with the provision of healthy food in school environments and the challenges of the practice itself. Starting from the question of how urban school gardens are effective, we sought to discuss how they are appropriate in the teaching-learning activities about the environmental issues, analyzing the obstacles to their incorporation as a teaching tool. Likewise, we sought to understand how the food produced in the gardens is used in school meals and how maintenance activities are carried out. Methodologically, the research has a qualitative nature and is based on technical procedures of bibliographic, documental and participant observation research, semi-structured interviews and photographic records. As an analytical object, the research relies on the study of multiple cases of four school gardens implemented in the year 2021, in the cities of Anápolis, Catalão, Rio Verde and Ouvidor, in the State of Goiás. The results indicate that, although school gardens are difficult to maintain, they benefit school meals by offering quality food, in great variety and quantity. At the same time, they have potential uses as an educational tool in the development of education activities for the teaching of environmental sustainability.